Anatomy of gene regulation : a three dimensional structural analysis - Tsonis, Panagiotis A. (Cambridge University Press, 2003)
No longer simple line drawings on a page, molecular structures can now be viewed in full-figured glory, often in color and even with interactive possibilities. Anatomy of Gene Regulation is the first book to present the parts and processes of gene regulation at the three-dimensional level. Vivid structures of nucleic acids and their companion proteins are revealed in full-color, three-dimensional form. Beginning with a general introduction to three-dimensional structures, the book looks at the organization of the genome, the structure of DNA, DNA replication and transcription, splicing, protein synthesis, and ultimate protein death. Throughout, the text employs a discussion of genetics and structural mechanics. The concise and unique synthesis of information will offer insight into gene regulation, and into the development of methods to interfere with regulation at diseased states. This textbook and its accompanying web site are appropriate for both undergraduate and graduate students in genetics, molecular biology, structural biology, and biochemistry courses.